Analysis of Student Readiness for Online Learning at the University of Nueva Caceres, Philippines: A Case Study at the College of Arts and Sciences during The Covid-19 Pandemic - Basbas, Maria Marietta (The Indonesian Institute of Science and Technology Research, 2024)
The educational sector has been one of the most impacted by the COVID-19 pandemic. The unexpected change from a brick-and-mortar school setting to an online platform became mandatory. Universities and colleges, as the central part of Higher Education Institutions, are considered essential sectors that involve a different level of students who represent the future potential human labor force. Therefore, it is necessary to understand the online learning readiness of the students in this current set-up. This investigation aimed to examine the students' readiness for online learning of the College of Arts and Sciences students during the COVID-19 pandemic. This research also acknowledged that preparedness for online learning would vary according to the student's characteristics. The respondents were 163 CAS students. The Student Readiness in Online Learning (SROL) was used to measure student readiness in online learning. It was found that students are ready in communication and online student attributes and in approaching technical and time management readiness. Strong associations were found between time management and technical subscales along with the demographic factors’ year level of the students and learning modality. Overall, online learning readiness had a strong association with the learning modality of the students. It was concluded that students have limited skills and knowledge to apply a given task independently, which limits effective and successful learning outcomes that are apparent in managing their time well. It is recommended that these skill gaps be addressed to reduce concerns of students from falling behind.